2018
DOI: 10.1021/acs.langmuir.8b00882
|View full text |Cite
|
Sign up to set email alerts
|

Inward Budding and Endocytosis of Membranes Regulated by de Novo Designed Peptides

Abstract: Protein-mediated endocytosis of membrane is a key event in biological system. The mechanism, however, is still not clear. Using a de novo designed bola-type peptide KKKLLLLLLLLKKK (KLK) as a protein mimic, we studied how it induced giant unilamellar vesicle (GUV) to form inward buds or endocytosis at varying conditions. Results show that the inward budding is initiated as the charged lipids are neutralized by KLK, which results in a negative spontaneous curvature. If the charged lipids have unsaturated tails, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 65 publications
2
8
0
Order By: Relevance
“…At the same time, deep insertion may induce negative curvature (Figure S1). Membrane deformation by electrostatic wrapping, and the neutralization of negatively charged lipids has also been reported as additional factors to induce negative curvature in a model membrane system. ,, We, therefore, hypothesized that invagination of cell membranes (plasma membranes) could be promoted by adding amphiphilic peptides having a negative-curvature propensity to living cells, resulting in the modulation of endocytosis and other cellular functions (Figure ). Endocytosis is a fundamental process in all eukaryotic cells by which extracellular materials are taken up by the invagination of the membrane to form encapsulating vesicles .…”
mentioning
confidence: 99%
“…At the same time, deep insertion may induce negative curvature (Figure S1). Membrane deformation by electrostatic wrapping, and the neutralization of negatively charged lipids has also been reported as additional factors to induce negative curvature in a model membrane system. ,, We, therefore, hypothesized that invagination of cell membranes (plasma membranes) could be promoted by adding amphiphilic peptides having a negative-curvature propensity to living cells, resulting in the modulation of endocytosis and other cellular functions (Figure ). Endocytosis is a fundamental process in all eukaryotic cells by which extracellular materials are taken up by the invagination of the membrane to form encapsulating vesicles .…”
mentioning
confidence: 99%
“…27 Moreover, a similar finding was elucidated by Yu et al, where they showed that no inward budding induced by the peptide K 3 L 8 K 3 took place in DOPG/ DOPC/DPPC GUVs when cholesterol is absent. 43 The authors further emphasize the contribution of hydrophobic interactions between the peptides and the vesicles to the observed deformations. Nevertheless, obtaining such information is not inherent in vesicular systems.…”
Section: Morphology Deformations Of Dopc/chol Guvsmentioning
confidence: 91%
“…Then, nanoparticles were incubated with cells at a final nanoparticle concentration of 100 µg mL −1 . Both CIS@M-F and CIS@M-C were labeled with Rhodamine B following a published protocol [ 65 ]. Following either 2 or 6 h of incubation, cells were harvested for flow cytometer analysis, and the MFI was recorded.…”
Section: Methodsmentioning
confidence: 99%